Do Police Body-Worn Cameras Reduce Citizen Fatalities? Results of a Country-Wide Natural Experiment - Miller, Joel (Journal of quantitative criminology, 2022)
Objectives This study assesses the effects of body-worn cameras (BWCs) on rates of fatalities arising from police-citizen encounters. While existing experimental research has not examined this outcome because it is so rare, the staggered roll-out of BWCs across the nation’s law enforcement agencies provides an opportunity for quasi-experimental analysis. Methods Difference-in-difference (DID) analyses using Poisson models compare changes in U.S. law enforcement agencies’ fatality counts with changes in BWC acquisition. Using a federal law enforcement survey focused on body worn cameras (LEMAS-BWCS) and media-sourced data on fatal encounters from fatalencounters.org (FE), the research examines agencies acquiring BWCs between 2013/14 and 2015/16 and those that did not acquire them up to 2016 and had no plans to do so. It includes a fixed effects annual panel data analysis with data from 2005/06 to 2018/19 and two two-group analyses focusing on a pre-treatment period (2010/11 to 2012/13) and a post-treatment period (2016/17 to 2018/19). The latter includes a propensity score matched comparison. Results Two out of three DID analyses showed statistically significant negative effects of BWCs on citizen fatalities. The propensity score matched two-group analysis returned a non-significant negative effect. Conclusions The research finds some evidence for BWC effects on citizen fatalities. However, there are important validity threats to this conclusion. These include the possibility that BWC acquisition serves as a marker for other policy changes focused on BWC-acquiring agencies in the 2013/14 to 2015/16 period and beyond.